Juvenes - The Middle Ages seen by Young Researchers Vol. II - Space(s) - Silva, André Filipe Oliveira da; Coelho, André Madruga; Simões, José; Sousa, Silvana R. Vieira de (Biblioteca - Estudos & Colóquios, 2022)
This volume publishes some of the texts presented at the 2nd edition of the International Congress for Young Researchers in Middle Ages, under the theme "Space(s)", held at the University of Évora between the 13th and 15th November 2019. As in the previous volume, the texts are authored by young researchers in medieval history, coming from various academic and geographical origins and combining various scientific disciplines.